Brazil's South–South development cooperation: Principles and experiences of the domestic bureaucracy. (23rd April 2018) - Farias, Deborah BL
Summary: How did Brazilian bureaucrats view President Lula's approach to the provision of development assistance in the context of South–South cooperation (SSC)? How did they see their own bureaucracy's role, as a provider of such assistance? This paper addresses these questions within the broad context of Brazil's development assistance program. The analysis begins with an elaboration of the internal legal and political structure supporting the country's provision of development assistance. Then, it addresses the research questions by drawing on original material obtained from 54 interviews, conducted in Brasilia, with diplomats and public servants from 25 federal ministries and institutions directly involved with implementing technical cooperation agreements. Evidence leads to three main observations: (a) the bureaucracies' limited autonomy vis‐à‐vis the Presidency's command of the Brazilian development assistance program; (b) great convergence in the worldviews and principled values upheld by public servants and diplomats in regard to Brazilian foreign policy; and (c) the existence of interbureaucracy complaints and struggles related to the operational side of agreement implementation. These findings are relevant for understanding the inner workings of Brazilian SSC, as well as in comparison to other national bureaucracies' involvement in the conceptualization and implementation of South–South knowledge transfers.